The Development of a Triage Model for Emergency Patients Using a Smartphone Application - Oura, Anusorn; Cheevakasemsook, Aree; Jetinai, Kotchakorn (Journal of The Royal Thai Army Nurses, 2025)
The objectives of this research were: (1) to explore the emergency triage situation, (2) to develop a smartphone application model for emergency patient triage, and (3) to study the effect of using the enveloped emergency patient triage model. This research and development project was divided into three phases. For Phase 1, studying the emergency triage situation, eight key informants were selected by purposive sampling, consisting of 1 doctor, 1 supervisory nurse, and six staff nurses. For Phase 2, developing an emergency triage model using a smartphone application, the key informants were the same as in the first phase. For Phase 3, applying the model, the samples comprised 184 emergency patients which were gathered by systematic random sampling and calculated using G power Data were analyzed using descriptive statistics and Mann-Whitney U test. The research found that emergency triage was incomplete, with disconnected information systems and nurses lacking expertise. Triage processes were inconsistent and inaccurate, falling below standards. A new emergency triage model was developed as a smartphone app using the National Institute of Emergency Medicine’s criteria. The user-friendly interface simplified triage with predefined lists. The app improved triage time and accuracy significantly. The average triage time was reduced to 50.85 seconds, and accuracy was statistically higher than traditional methods at the level of .001